O efeito moderador da orientação a metas na relação entre as características do gerente de projetos e o sucesso do projeto - Suzuki, Fernando Cesar Barros (2021)
Projects are increasingly important in companies due to their direct relationship with the performance of the organizations. This importance is driven by the business value and strategic objectives that the projects generate, developing a competitive advantage, despite the fact that some data indicate that a significant number of projects fail. The project manager is recognized as a responsible agent for the performance of the project with the recognition that one of the fundamental factors for the success of the projects is the set of characteristics of the managers. The Upper Echelon Theory (UET) portrays that organizational results and performance levels result from the top management team’s characteristics. However, there is a gap to be explored, which is the middle managers’ role, in this case, the project manager. One of the fundamental concepts of UET is managerial discretion. In this research, I investigate the moderating effect of goal orientation on the influence of the project manager’s manager on the success of the projects in which goal orientation may influence the managerial discretion. The expected contribution to the theory is the understanding of the impact of the project manager on the success of the projects. The contribution to the practice is the development of a framework as a guide for company executives or managers regarding the influence of the project manager on the success of projects and the presentation of specific attributes of the project manager, which can contribute to the success of the project.